Development of genetic stocks of sunflower with resistance to sunflower chlorotic mottle virus = Conformación de recursos genéticos de girasol con resistencia al virus del moteado clorótico del girasol - Fernández Moroni, Ivana; Lenardon, Sergio Luis; Giolitti, Fabian; Alvarez, Daniel; Poverene, María Mónica; Presotto, Alejandro Daniel; Cantamutto, Miguel Angel (Sociedad Argentina de Genética, 2024)
The common race of sunflower chlorotic mottle virus (SCMoV-C) can cause severe yield losses in susceptible genotypes of sunflowers if infection occurs at early plant stages. In Argentina, SCMoV-C is widespread in sunflower production fields and even if its incidence is generally low, in some cases it can reach up to 95%. To date, no complete resistance to SCMoV-C has been detected in commercial cultivars. In the search for resistant germplasm, wild sunflower (Helianthus annuus L.) populations from Argentina were tested, as they were exposed to natural selective pressure during their naturalization. After artificial inoculation with SCMoV-C, symptom-free plants were selected and grown for controlled self-pollination, sibling crosses and crosses with inbred lines. Recurrent selection for non-symptomatic plants and self-fertility significantly increased the frequency of asymptomatic individuals after SCMoV-C inoculation in the development germplasm. After eight generations of recurrent selection and controlled crosses, four genetic stocks with complete SCMoV-C resistance were developed.